Advertisements or friends? Formal and informal recruitment methods in Tanzania - Henrik Egbert; Gundula Fischer; Sebastian Bredl (Justus-Liebig-Universität Gießen, Zentrum für Internationale Entwicklungs- und Umweltforschung (ZEU), 2009)
Only insufficient data are available on the recruitment methods of enterprises in Africa. Our aim is to investigate the recruitment methods of small and medium sized private companies in Tanzania. We test whether the way formal and informal methods are employed is similar or different to the way they are employed by companies in Europe or North America. Data collected by half-standardized questionnaires in Mwanza show that informal methods (such as referrals by friends) are primarily applied for low-ranking positions while formal methods, particularly newspaper advertisements, are used for high-ranking positions. This stands in contrast to findings from industrialized countries where informal methods are more important for filling high-ranking positions. For the vacancy period of high- and lowranking positions patterns do not differ from those in industrialized countries.
Keywords: 330